Tailoring the Interfacial Band Offset by the Molecular Dipole Orientation for a Molecular Heterojunction Selector (Adv. Sci. 21/2021). Issue 21 (3rd November 2021) - Eo, Jung Sun; Shin, Jaeho; Yang, Seunghoon; Jeon, Takgyeong; Lee, Jaeho; Choi, Sanghyeon; Lee, Chul‐Ho; Wang, Gunuk
Abstract : Molecular Heterojunction In article number 2101390 by Gunuk Wang and co‐workers, a tailored molecular heterojunction selector is implemented by controlling its interfacial band offset. Based on diverse interfacial band offsets achieved by changing the heterojunction constituents, such as the molecular dipole moment direction, types of two‐dimensional transition metal dichalcogenide, and work function of the electrodes, the nonlinearity is widely tuned. The suggested molecular heterojunction selector is depicted in array and binary numbers.